2021
DOI: 10.1007/s00281-021-00864-x
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity in hepatitis B and D virus infection: consequences for viral persistence, inflammation, and T cell recognition

Abstract: Chronic infections with human hepatitis viruses continue to be a major health burden worldwide. Despite the availability of an effective prophylactic vaccine against the hepatitis B virus (HBV) and of antiviral agents efficiently suppressing HBV replication, more than 250 million people are currently chronically infected with this hepatotropic DNA virus, and resolution of chronic hepatitis B (CHB) is rarely achieved. Moreover, coinfection with the hepatitis D virus (HDV), a human RNA satellite virus requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 134 publications
2
23
0
Order By: Relevance
“…It even has been suggested that some innate pathways support HDV replication productivity [40], since the IFN system induces RNA-editing enzyme adenosine deaminase (ADAR), which is required for RNA editing to generate L-HDAg, and hence enables viral morphogenesis [45]. It is important to note that MDA-5-mediated production of IFN and ISG induction also contributes to a cytokine milieu that recruits professional antigen-presenting cells, and thus enables priming of functional T cells [46].…”
Section: Innate Immunitymentioning
confidence: 99%
“…It even has been suggested that some innate pathways support HDV replication productivity [40], since the IFN system induces RNA-editing enzyme adenosine deaminase (ADAR), which is required for RNA editing to generate L-HDAg, and hence enables viral morphogenesis [45]. It is important to note that MDA-5-mediated production of IFN and ISG induction also contributes to a cytokine milieu that recruits professional antigen-presenting cells, and thus enables priming of functional T cells [46].…”
Section: Innate Immunitymentioning
confidence: 99%
“…In contrast, liver damage during chronic HBV infection is mainly attributed to dysregulated activation of intrahepatic immunity leading to nonspecific hepatocyte killing [56][57][58][59]. By acquiring exhaustive phenotypes and producing less inflammatory chemokines and cytokines, it is believed that CD8+ T cells may not be the major mediator of hepatic injury.…”
Section: Host Immunity and Liver Damage During Hbv Infectionmentioning
confidence: 99%
“…The above findings demonstrated that dynamic interactions of the virus, and innate (including cytokines and chemokines) and adaptive immune responses contribute to the development of hepatitis B flare in patients with CHB [16,57,58,63]. In this review, we will mainly focus on the role of cytokines and chemokines.…”
Section: Host Immunity Profile During Af Of Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections with hepatitis viruses are a major trigger of chronic liver inflammation and liver disease. In this issue, Dandri et al discuss the innate immune response in viral hepatitis, its consequences for T cell recognition and how this impacts on viral persistence or clearance [8]. The authors elucidate viral strategies to manipulate and shape the immune response and therapeutic strategies that might specifically target viral evasion.…”
Section: Homoeostatic Inflammation Vs Pathogenic Tissue Remodellingmentioning
confidence: 99%